When Does Status Transfer between People? A Crowdsourced Experiment on the Scope of Status by Association. (December 2021) - Overton, Jon
It is well known in social psychology that people are judged by the company they keep, but when and how does that company affect how individuals are evaluated? This article extends expectation states theory to explain associative status. The theory predicts that the status value of former coworkers will "spill over" to positively predict a person's status position in a new task with new coworkers. A series of crowdsourced experiments finds that status spreads to a person from a former interaction partner. The status of one's associates predicts deference behavior only when the previous and current task contexts rely on similar abilities. Meanwhile, explicitly evaluated status and performance expectations respond to the status of associates regardless of how interaction contexts are related. The present findings highlight the importance of role relationships and task contexts as moderators that regulate whether status transfers from one person to another.